Transient stability mechanism of grid-connected inverter-interfaced distributed generators using droop control strategy. (15th January 2018) - Yu, Moduo; Huang, Wentao; Tai, Nengling; Zheng, Xiaodong; Wu, Pan; Chen, Weidong
Highlights: This paper presents the transient stability mechanism of IIDGs. The transient stability sensitivity to droop factors is proposed. The relation between the network parameters and IIDG's transient stability is analyzed. A accurate transient stability judgment is designed. Abstract: The large-scale application of renewable energy is promising to solve the energy crisis over the world. Renewable energy is generally integrated into distribution networks or microgrids through inverters. Inverter-interfaced distributed generators (IIDGs) have the advantage of utilizing renewable energy effectively and flexibly. However, the wide interconnection of IIDGs causes transient stability to the public grid. This paper presents the transient stability mechanism of the grid-connected IIDGs using droop control. The transient stability mechanism is obtained by combining the transient stability condition and the comprehensive dynamic trace. The transient stability condition is proposed by the transient model and IIDGs' operation features. The comprehensive dynamic trace is formulated by the active and reactive power curves during transient events. The mechanism is able to reflect the relations between transient stability and droop factors and reveal the transient behaviors of IIDGs. The transient stability judgment is correspondingly developed. A series of simulations demonstrate the correctness and effectiveness of the transient stability mechanism. The transient stability mechanism better expands and develops the utilization of renewable energy.